Heterogeneity and Plasticity of Human Breast Cancer Cells in Response to Molecularly-Targeted Drugs - Bousoik, Emira; Nabiee, Ramina; Amirrad, Farideh; Nichols, Ashley; Witt, Rebecca; Mahdipoor, Parvin; Montazeri Aliabadi, Hamidreza (Frontiers in Oncology, 2019)
Non-responsive subpopulation of tumor cells, and acquired resistance in initially responsive cells are major challenges for cancer therapy with molecularly-targeted drugs. While point mutations are considered the major contributing factor to acquired resistance, in this study we explored the role of heterogeneity and plasticity of selected human breast cancer cell lines (MDA-MB-231, MDA-MB-468, and AU565) in their initial and adjusted response, respectively, to ruxolitinib, everolimus, and erlotinib. After determination of lethal concentration for 50% cell death (LC50), cells were exposed to selected drugs using three different approaches: single exposure to 4 x LC50 and collection of surviving cells, multiple exposures to 1.5 x LC50 and monitoring the surviving population, and exposure to gradually increasing concentrations of selected drugs (range of concentrations equivalent to 10% of LC50 to 1.5 x LC50). Surviving cells were studied for adjustments in expression level of selected proteins using quantitative PCR and Western Blot. Our data indicated overexpression of a variety of proteins in resistant populations, which included cell membrane receptors EGFR and HER2, anti-apoptotic proteins Bcl-2 and BIRC8, and other proteins involved in cell signaling (e.g., Akt1, MAPK7, and RPS6KA5). Silencing the identified alternative proteins via siRNA resulted in significant drop in the LC50 of the selected molecularly-targeted drugs cells resistant to ruxolitinib (via targeting Akt), everolimus (via targeting EGFR, MAPK7, RPS6KA5, and HER2), and erlotinib (via silencing Bcl2 and BIRC8). Our data indicates that targeting well-selected alternative proteins could potentially sensitize the resistant cells to the effect of the molecularly-targeted treatment.